1009 Sleep Apnea and Colorectal Adenoma in the Veteran Population: A Case-Control Study. (27th May 2020) - Guan, L; Jiao, L; Malhotra, S
Abstract: Introduction: Colorectal cancer is the third most common cancer in the United States, with over half of colorectal cancers estimated to be the result of modifiable risk factors. Studies relating sleep apnea (SA) and colorectal adenoma (CRA) are limited and the findings are equivocal. The objective of this study was to examine the association between SA and risk of CRA. Methods: This was a retrospective cross-sectional case-control study of data collected from 460 veterans, ages 50-79, seen in the colonoscopy clinic at the Michael E. DeBakey VA Medical Center between 2014 and 2018. Information on demographics, sleep history, and co-morbidities were obtained through lifestyle questionnaire. Self-reported SA was diagnosed by a prior sleep study. Cases consisted of 297 participants had pathologically confirmed adenoma (including 117 participants having advanced CRA with villous component or diameter of polyp > 1 cm). Controls consisted of 173 polyp-free participants. The distribution of demographics and lifestyle factors were compared between CRA and non-CRA using the Student's t or chi-square tests. Odds ratios (OR) and 95% confidence intervals (CI) of CRA in association with CRA were calculated using univariate and multivariate unconditional logistic regression models. The confounding factors included age, sex, ethnicity, obesity, smoking status, alcohol use, hypertension, and sleep duration. Results: Compared with non-SA, the multivariable OR (95% CI) for CRA was 0.92 (0.58-1.48); for non-advanced CRA was 1.14 (0.68-1.91), and for advanced CRA was 0.61 (0.32-1.17) in SA participants. Adjustment of sleep duration in the model did not change the risk estimates. Conclusion: Sleep-study diagnosed SA was not associated with development of CRA in this veteran population. Further studies are needed to confirm this observation and incorporate the severity and treatment of SA, and undiagnosed SA in risk assessment. Support: This research is supported in part by the Gillson Longenbaugh Foundation, and Golfers Against Cancer organization (to LJ), the Cancer Prevention Research Institute of Texas (CPRIT) (RP#140767, to LJ).